Histopathological Changes of Egg Cells in the Uterine of Ascaridia galli after Treatment with Extract of Veitchia merrillii Nuts - Ummu Balqis; Muslina Muslina; Muhammad Hambal; Farida Athaillah; Muttaqien Muttaqien; Azhar Azhar; Ismail Ismail; Rastina Rastina; Eliawardani Eliawardani; Abdul Harris; Abdullah Hamzah; Henni Vanda; Darmawi Darmawi (Majalah Obat Tradisional, 2017)
The aim of the study was to observe the histopathological changes of the entire egg cells in the uterine of Ascaridia galli worms treated with crude ethanolic extract of Veitchia merrillii nuts. Histopathological changes of the entire egg cells were observed to describe that the activity of extract V. merrillii nuts interfered the reproduction process could decrease the quantity and quality of A. galli eggs. The experiments consisted of 16 head A. galli female adult worms divided into four groups, contained four worms of each, and maintained in 0.9% phosphate buffered saline (PBS). First group, a negative control experiment consisted of A. galli in 0.9% PBS. Second group, concentration of 15 mg/mL albendazole was used as a positive control. Third group and fourth group, in vitro exposure of the worms to the crude ethanolic extract V. merrillii nuts at a concentration of 25 mg/mL and 75 mg/mL, respectively. The histopathological changes of egg cells in the uterine region of stained worms was evaluated by light microscopic examination at 40x magnification. The results showed that shrinkage and disintegration of the entire egg cells in the breakage of uterus. The results indicate that the possible use of the plant as a potential anthelmintic against A. galli, the intestinal nematode parasite of domestic fowl.